Postcoloniality Without Race? Racial Exceptionalism and Southeast European Cultural Studies. Issue 6 (18th August 2018) - Baker, Catherine
Abstract : The black Dutch feminist Gloria Wekker, assembling past and present everyday expressions of racialized imagination which collectively undermine hegemonic beliefs that white Dutch society has no historic responsibility for racism, writes in her book White Innocence that "one can do postcolonial studies very well without ever critically addressing race." Two and a half decades after the adaptation of postcolonial thought to explain aspects of cultural politics during the break-up of Yugoslavia created important tools for understanding the construction of national, regional, and socioeconomic identities around hierarchical notions of Europe and the Balkans in the Yugoslav region and beyond, Wekker's observation is still largely true for Southeast European studies, where no intervention establishing race and whiteness as categories of analysis has reframed the field like work by Maria Todorova on "balkanism" or Milica Bakić-Hayden on "symbolic geographies" and "nesting orientalism" did in the early 1990s. Critical race theorists such as Charles Mills nevertheless argue that "race" as a structure of thought and feeling that legitimized colonialism and slavery (and still informs structural white supremacy) involved precisely the kind of essentialized link between people and territory that Southeast European cultural theory also critiques: the construction of spatialized hierarchies specifying which peoples and territories could have more or less access to civilization and modernity. Southeast European studies' latent racial exceptionalism has some roots in the race-blind anticolonial solidarities of state socialist internationalism (further intensified for Yugoslavia through the politics of Non-Alignment) but also, this essay suggests, in deeper associations between Europeanness, whiteness, and modernity that remain part of the history of "Europe" as an idea even if, by the end of the twentieth century, they were silenced more often than voiced.